Degeneracy in Heteroscedastic Regression Models - Li, Kim-Hung; Chan, Nai Ng (Journal of multivariate analysis, 2000)
The maximum likelihood estimation in a regression model with heteroscedastic errors is considered. When the design matrices in the model are inappropriately specified, the maximum likelihood estimates of the variances of certain observations are found to be zero irrespective of the observed values, resulting in degeneracy. Necessary and sufficient conditions for degeneracy are given and used for its avoidance.